The Effect of the Problem-Based Learning Model on Students’ Learning Motivation in Social Arithmetic Materials - Erpina Ulva; Atma Murni (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This study aimed to determine the effect of the Problem Based Learning (PBL) model on students' learning motivation on Social Arithmetic material. This study was conducted to see the effect of the application of the PBL model on students' learning motivation in terms of the overall high-level students in the research sample. This study uses an experimental method with a pretest-posttest control group design. The population in this study were seventh-grade students of State Junior High Schools in Kuantan Regency. The population comes from high-level schools. The sample in this study was SMP Negeri 1 Taluk Kuantan (high level). There was one experimental class and one control class in the schools that became the research sample. The results showed that it was significant 0.000 < 0.05, which means that there is an effect of the application of PBL on students' learning motivation in terms of all students in which students' learning motivation using the PBL model is better than students using conventional learning.